THE FORECASTING OF STATE PARAMETERS OF THE TRANSPORT SYSTEMS WITH REGARD TO EVOLUTIONARY PROCESSES - Hryhorov, M. A.; Sanko, Ya. V. (Science and Transport Progress, 2008)
The considered regularities of determination of closed and opened state of system parameters on the basis of entropic characteristics and evolution processes in the environment allow predicting the duration of these periods with certain precision.